Entrepreneurship education research in Nigeria: current foci and future research agendas. Issue 2 (11th June 2018) - Yatu, Lemun; Bell, Robin; Loon, Mark
Abstract : Purpose: Entrepreneurship education plays a crucial role in the development of entrepreneurs and the enhancement of entrepreneurial activities in every economy. This paper presents the findings of a review of Nigerian entrepreneurship education literature published in 20 journals over a 16-year period. The purpose of this paper is to examine research contributions in the field of entrepreneurship education within the Nigerian context, with the aim of understanding the focus and the different research areas covered by researchers in this area, and to make suggestions that can guide scholars in their future research contributions. Design/methodology/approach: Systematic literature reviews are recognized methods for conducting evidence-based research. The study adopted a systematic literature review approach, drawing from a computerized search of five selected databases, using predetermined key words by the researchers. Findings: The main finding of this paper is that related concepts like skills, intention, drive and attitude have been used in expounding discussions on the outcome of entrepreneurship education, but very little has been written on entrepreneurial mindset, which other studies have suggested is a crucial point in the journey of an entrepreneur (Reed and Stoltz, 2011; Neneh, 2012). Furthermore, learning and teaching of entrepreneurship in the Nigerian higher education institutions seem to be more focused on creating awareness about entrepreneurship, as against the experiential approach that scholars have argued to be a prerequisite for developing the next generation of entrepreneurs (Bell, 2015 ). The study also found that over 80 percent of the reviewed articles are published in journals not ranked or indexed in the ABS journal rankings or the Scopus database. Research limitations/implications: The paper is limited since it is based on a review of literature from a selected range of databases, covering a specific time span. This potentially excludes other studies outside this time span. Scholarship in this area and context will benefit greatly when researchers target, choose and engage the higher ranked and more impactful journals as the outlet for their research outputs. Practical implications: At a time when efforts are being made to address socioeconomic issues like poverty and unemployment through mainstream training in entrepreneurship education, this paper provides a better understanding of the state of research in this context, by highlighting the potential gaps as to where research investigation is needed for better policy formulation and guiding future research. Originality/value: There are limited studies that focus on the issue of entrepreneurial mindset in entrepreneurship education in Nigeria. Overall, this paper identifies an important gap in the literature that warrants future research.